DEVELOPING THE MATHEMATICS STUDENT ACTIVITY SHEET (SAS) IN MATTER CIRCLE FOR STUDENTS OF SMP/MTs CLASS VIII BASED PROBLEM - Adam Sukrulilla; Sunaryo Sunaryo (Universitas Ahmad Dahlan, 2017)
This research is motivated by the lack of Student Activity Sheet (SAS) in the study of mathematics for students of class VIII SMP/MTs. The purpose of this research is to develop a SAS based problem, determine eligibility based on expert assessment and teacher assessment, as well as students' response to SAS. The study was conducted through the model of Research and Development(R &D). Steps that passed include two aspects, namely the development of the SAS and its feasibility. SAS development includes: (a) collecting information (b) the designing of SAS(c) Validating SAS to the expert review by the mathematics teacher of MTs N 2 Yogyakarta and SMP Muhammadiyah 6 Yogyakarta (d) revising the product. The feasibility of SAS include (a) trial test (b) data analysis(c) the feasibility of SAS. The subjects were students. Data were analyzed using qualitative descriptive analysis to describe the inputs from expert assessment of products, SAS assessment by expert assessment of products, teachers and students' responses to the SAS based problem. The results of research and development has developed the Student Activity Sheet (SAS) on the circle in class VIII SMP/MTs based problem. The results of expert assessment and teacher assessment on the products obtained an average score of 75with good category, so the SAS can be declared feasible. The students' response to the SAS is included in very good categories indicated by an average score of 87, 7093335. These results indicate that the Student Activity Sheet (SAS) in the circle in class VIII of SMP/MTs based problems can be used in the learning process.